2022
DOI: 10.1007/s00259-022-05712-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative classification and radiomics of [18F]FDG-PET/CT in indeterminate thyroid nodules

Abstract: Purpose To evaluate whether quantitative [18F]FDG-PET/CT assessment, including radiomic analysis of [18F]FDG-positive thyroid nodules, improved the preoperative differentiation of indeterminate thyroid nodules of non-Hürthle cell and Hürthle cell cytology. Methods Prospectively included patients with a Bethesda III or IV thyroid nodule underwent [18F]FDG-PET/CT imaging. Receiver operating characteristic (ROC) curve analysis was performed for standardised u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Six studies were available for thyroid tumors [ 222 , 223 , 224 , 225 , 226 , 227 ], all using 18F-FDG. The average number of patients was 89.0 (range 55–123); 3/6 (50.0%) studies included more than 100 patients, 1 was prospective and 1 used a validation cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were available for thyroid tumors [ 222 , 223 , 224 , 225 , 226 , 227 ], all using 18F-FDG. The average number of patients was 89.0 (range 55–123); 3/6 (50.0%) studies included more than 100 patients, 1 was prospective and 1 used a validation cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 3/6 (50.0%) studies focused on 18F-FDG thyroid incidentalomas, 2 studies were interested in risk stratification in indeterminate thyroid nodules. The only study with a QS above 3, a prospective study of 123 patients conducted by de Koster et al [ 225 ], reported no added value of radiomics for that purpose in 18F-FDG positive nodules.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies used outdated data to explore the incidence of TC, while GBD 2019 provided the latest population-based cancer registration data, which estimated the burden of 285 diseases and disabilities using a uniform and standardized approach. This study will compare the data of different countries/regions and different periods through GBD 2019 in order to provide data support for the rational allocation of medical resources and the establishment of prevention and screening system ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathak et al reported a SUV max cut-off of 3.25 g/mL best differentiated 42 non-Hürthle cell nodules with 79% sensitivity and 83% specificity [297]. An additional analysis of the EfFECTS trial dataset assessed the added value of SUV metrics, SUV-ratios (node to contralateral normal thyroid) and radiomics for the preoperative differentiation [293].…”
Section: Increased [ 99mmentioning
confidence: 99%
“…None of these previous studies used ROC curve analysis to determine SUV cut-offs that corresponded to optimal test sensitivity, i.e., a NPV similar to a benign cytologic diagnosis (i.e., 96.3%) as per the ATA recommendations for a useful rule-out test [205]. De Koster et al performed quantitative analysis and ROC curve analysis of the EfFECTS dataset, including 123 patients who underwent [ 18 F]FDG PET/CT according to the EANM guidelines [293]. Quantitative [ 18 F]FDG PET/CT assessment ruled out malignancy in indeterminate thyroid nodules, optimising the rule-out ability when distinctive SUV cut-offs were applied to Hürthle and non-Hürthle cell nodules.…”
Section: Increased [ 99mmentioning
confidence: 99%